Qualitative studies of silence : the unsaid as social action - Murray, Amy Jo; Durrheim, Kevin (Cambridge University Press, 2019)
Qualitative Studies of Silence brings together influential qualitative researchers from across the social sciences and humanities who have sought to understand the power of what remains unsaid, both psychologically and socially. Each chapter identifies one or more signs of silence and explains how these can form the basis of a rigorous qualitative investigation. The authors also demonstrate how silences operate in our private and collective lives by fulfilling psychological, relational, institutional, and ideological functions. The book contains multiple disciplinary perspectives and presents analyses of wide-ranging topics, such as medical consultations, whistleblowers, silence in court, omission-as-propaganda, trauma survivors, the silence of war museums, racism in the Americas, gendered silences, paid domestic labour, the undocumented student movement, and the Nazi past. This collection shows how such qualitative studies can reveal and contribute to understanding the unsaid as social action.